Terapia dialéctico conductual en la reducción de la conducta suicida en adolescentes - Toledo Sarango, María Emilia (2023)
Dialectical Behavior Therapy is an intervention developed for the treatment of Borderline Personality Disorder, symptomatology related to emotional dysregulation and suicidal behavior, which has been adapted to different age groups, including adolescents. However, due to the limited number of studies of this therapy at national level, added to the limited number of researches in our language, and the complexity of the problem of suicidal behavior, linked to the increase of its prevalence in adolescents, and adding the need to know new effective interventions for treatment. The aim of this research was to describe the scientific evidence of Dialectical Behavior Therapy in the reduction of suicidal behavior in adolescents. In which, a bibliographic documentary study was established, with a descriptive, quantitative, cross-sectional design, based on the review, selection and analysis of a sample of 15 scientific articles, in relation to the study variables, with inclusion and exclusion criteria, such as age range (12-18 years), articles published in the last 10 years and that are research with quantitative results for analysis, obtaining beneficial results regarding the use of therapy, where a decrease in the symptomatology of suicidal behavior was evidenced, while examining different clinical pictures treated under this therapy, obtaining the depressive disorder as the most prevalent picture, and finally, with the identification of risk factors that adolescents may present to increase the predisposition to suicidal behavior, such as previous suicidal behavior, and emotional dysregulation